Interleukin-6-elicited chronic neuroinflammation may decrease survival but is not sufficient to drive disease progression in a mouse model of Leigh syndrome - Kevin Aguilar; Carla Canal; Gemma Comes; Sandra Díaz-Clavero; Maria Angeles Llanos; Albert Quintana; Elisenda Sanz; Juan Hidalgo (Journal of Inflammation, 2024)
Abstract Background Mitochondrial diseases (MDs) are genetic disorders characterized by dysfunctions in mitochondria. Clinical data suggest that additional factors, beyond genetics, contribute to the onset and progression of this group of diseases, but these influencing factors remain largely unknown. Mounting evidence indicates that immune dysregulation or distress could play a role. Clinical observations have described the co-incidence of infection and the onset of the disease as well as the worsening of symptoms following infection. These findings highlight the complex interactions between MDs and immunity and underscore the need to better understand their underlying relationships. Results We used Ndufs4 KO mice, a well-established mouse model of Leigh syndrome (one of the most relevant MDs), to test whether chronic induction of a neuroinflammatory state in the central nervous system before the development of neurological symptoms would affect both the onset and progression of the disease in Ndufs4 KO mice. To this aim, we took advantage of the GFAP-IL6 mouse, which overexpresses interleukin-6 (IL-6) in astrocytes and produces chronic glial reactivity, by generating a mouse line with IL-6 overexpression and NDUFS4 deficiency. IL-6 overexpression aggravated the mortality of female Ndufs4 KO mice but did not alter the main motor and respiratory phenotypes measured in any sex. Interestingly, an abnormal region-dependent microglial response to IL-6 overexpression was observed in Ndufs4 KO mice compared to controls. Conclusion Overall, our data indicate that chronic neuroinflammation may worsen the disease in Ndufs4 KO female mice, but not in males, and uncovers an abnormal microglial response due to OXPHOS dysfunction, which may have implications for our understanding of the effect of OXPHOS dysfunction in microglia.